Rising Sea-Level, Rising Threats - Muniruzzaman, A. N. M. (2017)
Backed by scientific data and evidences, Sea-level Rise (SLR) is no longer an issue of make-belief. Almost all states now agree to the emerging threats to security from climate change, especially risks from sea level rise to global peace and security.